Systémová a intraperitoneální inflamace u peritoneálně dialyzovaných pacientů - Opatrná, Sylvie (Vnitrni lekarstvi, 2016)
Any degree of microinflammation is an independent risk factor for mortality for patients with chronic kidney disease in all stages. During peritoneal dialysis, intraperitoneal activation of inflammation occurs, the degree of which in stable patients without infectious complications depends in particular on the content of peritoneal dialysis solution with regard to osmotic agents (glucose, icodextrin) and buffer (lactate, bicarbonate or their combination) which as the same time defines the level of biocompatibility of these solutions. The degree of intraperitoneal inflammation affects peritoneal permeability, however there is no evidence of it directly increasing the systemic inflammation and it does not correlate with mortality. On the other hand, the systemic inflammation affected in peritoneal dialysis patients primarily by age and comorbidities, i.e. factors independent of peritoneal dialysis alone, does predict long-term clinical results.Key words: biocompatibility - icodextrin - inflammation - peritoneal dialysis - peritoneal dialysis solutions.
Keywords: icodextrin; glukosa; Inflammation; Peritoneal Dialysis; lidé; hydrogenuhličitany; zánět; glukany; Icodextrin; Dialysis Solutions; Glucans; Peritonitis; peritoneum; peritoneální dialýza; Humans; Bicarbonates; peritonitida; Peritoneum; dialyzační roztoky; rizikové faktory; Risk Factors; Glucose